Activities Patients and Nurses Undertake to Promote Patient Participation. Issue 4 (19th May 2016) - Tobiano, Georgia; Marshall, Andrea; Bucknall, Tracey; Chaboyer, Wendy
Abstract: Purpose: To describe and understand activities patients and nurses undertake to enact patient participation in nursing care. Design: This observational study was conducted on two medical units at a public hospital in Australia. Twenty‐eight nurse–patient dyads were observed for at least 4 hr. Data were collected from November 2013 to February 2014. Methods: Field notes were collected and were analyzed both inductively and deductively. Findings: Nurse–patient interactions promoted patient participation through dialogue and knowledge sharing. Less evident was patient involvement in planning or self‐care. Nurses exerted control over patient care, which influenced the extent of patient participation. Conclusions: Patient participation appears to be difficult to enact. Nurses' controlling approach, influenced by organizational issues, was in conflict with a patient‐centered approach to care. Nurse–patient communication is one aspect of patient‐centered care enacted more frequently. Clinical Relevance: Nurses may benefit from strategies at the individual and organizational level to enhance their patient‐centered practices. Fostering nurses' communication may enhance patient‐centered practices in hospitals.